Correlations of Social Interaction and Digital Media Use With Mental Health Among Urban Adolescents: A Cross-sectional Study - Siti Jumhati (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Digital platforms are now central to adolescents' daily routines, yet their mental-health implications may reflect both online engagement and offline relationships. This cross-sectional study examined associations between social interaction, digital media use, and symptoms of depression, anxiety, and stress among urban adolescents in Jakarta, Indonesia. One hundred high-school students (13-18 years) were recruited purposively and completed structured Likert-type measures of social interaction and digital media indicators; mental health was assessed using DASS-21. Pearson correlation was applied (α=0.05). Nearly half of participants (48%) reported social media use exceeding five hours/day, and TikTok was the most frequently used platform (58%). At least moderate symptoms were reported by 64% for depression, 80% for anxiety, and 46% for stress. Longer daily use and higher perceived media pressure/self-perception influence were positively associated with higher DASS-21 scores (p<0.01 for duration). Conclusion: Offline social interaction and digital media engagement were both statistically related to adolescent mental-health symptoms, highlighting the need for school- and family-based support, digital literacy, and healthier online habits. Keyword: Adolescents Mental health, Social Interaction, Digital media, Social media